2021
DOI: 10.1108/gkmc-08-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive standards and collection management software for documentary heritage management: attitudes and experiences of information professionals

Abstract: Purpose This paper aims to examine the attitudes and experiences of information professionals with descriptive standards and collection management systems (CMSs) used for managing documentary heritage collections held by cultural heritage institutions in New Zealand (NZ). The aim is that such insights will inform decision-making around promoting documentary heritage collections discoverability and accessibility, in terms of advocating for appropriate system requirements when procuring or updating CMSs, and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The approach of bringing professionals from different fields into contact with each other should be accompanied by a modification of university curricula referring metadata specialists to make them less stratified and more interprofessional (Renshaw and Liew, 2021), so that metadata experts are able to adapt to a biodiversity collection, to a human heritage catalog and even to working in a library or archive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of bringing professionals from different fields into contact with each other should be accompanied by a modification of university curricula referring metadata specialists to make them less stratified and more interprofessional (Renshaw and Liew, 2021), so that metadata experts are able to adapt to a biodiversity collection, to a human heritage catalog and even to working in a library or archive.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors (Alexiev, 2018; Freire et al , 2019; Smith-Yoshimura, 2020) have identified linked open data and semantic data integration as key elements in this process. At the same time, it is important to consider the perspectives of authors such as Renshaw and Liew (2021), who suggest that convergence is increasingly being viewed as problematic because of the very different contexts of the various types of institutions involved.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…The need to improve the quality of cultural heritage metadata and collection management systems (CMSs) is stressed [35]. Metadata enrichment through crowdsourcing annotation services [32] and machine learning techniques [36][37][38][39] is recommended.…”
Section: Digitisation and Archivingmentioning
confidence: 99%
“…Memory institutions, especially those that function at a national level, are inherently political anyway by what they have historically selected to collect and preserve, and what they prioritise in their curation. The decisions they make about whose memories and history they preserve (Davidson, 2015), transmit and communicate, and how those records are represented and organised in their collections (Renshaw and Liew, 2021) are not necessarily apolitical. National memory institutions such as national libraries and national archives have a responsibility to the diverse communities they purport to represent through their collections.…”
Section: Social Media Risk Management For Memory Institutionsmentioning
confidence: 99%